Perinatal Outcome in Pregnant Females with Sepsis at a Tertiary Care Hospital - Nabeela Atta,; Muhammad Ramzan,; Sadaf-Un-Nisa,; Bilal Rafique Malik,; Rabia Bhatti,; Atif Maqsood, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Sepsis during pregnancy is a significant contributor to maternal mortality. Sepsis during pregnancy refers to the intricate pathological process that is further complicated by immune-modulatory changes specific to pregnancy. Maternal sepsis is linked to negative pregnancy outcomes. Objective: To determine the outcome of prenatal sepsis and maternal sepsis at a tertiary care Nishtar hospital, Multan. Methodology: This Retrospective study was conducted at Department of obstetrics and gynecology, Nishtar Hospital Multan from 1st July 2022 to 30th June, 2023. Females were enrolled from emergency department. Females were booked until delivery of baby and following outcomes were noted including mode of delivery, preterm birth, premature rupture of membranes (PROM), or miscarriage. All the data was recorded in proforma. Data was analyzed in SPSS version 25. Outcomes were presented as frequency and percentage. Results: In this study, mean age of females was 29.09 ± 3.02 Years. There were 120 (60%) obese females. The mean gestational age was 33.45 ± 7.42 weeks. PROM was observed in 126 (63.4%) females, miscarriage in 32 (16%) females and preterm delivery in 80 (40%) females. Out of 200 females, vaginal delivery occurred in 90 (45%) females while cesarean section in 110 (55%) females. Conclusion: The chances of adverse outcome of maternal and perinatal sepsis are high and leads to severe life risking prognosis. Therefore, not in future, we will implement counseling sessions during antenatal visits or after delivery for proper antenatal check-up, signs of sepsis and its hazardous consequences. Key words: Sepsis, Fetal Resorption, Outcomes, health.